Closing the Cycle as It Begins: Synthesis of ortho‐Iodobiaryls via Catellani Reaction. (27th March 2023) - Botla, Vinayak; Fontana, Marco; Voronov, Aleksandr; Maggi, Raimondo; Motti, Elena; Maestri, Giovanni; Della Ca', Nicola
Abstract: Despite the advances in the field of carbon‐halogen bond formation, the straightforward catalytic access to selectively functionalized iodoaryls remains a challenge. Here, we report a one‐pot synthesis of ortho ‐iodobiaryls from aryl iodides and bromides by palladium/norbornene catalysis. This new example of Catellani reaction features the initial cleavage of a C(sp 2 )−I bond, followed by the key formation of a palladacycle through ortho C−H activation, the oxidative addition of an aryl bromide and the ultimate restoration of the C(sp 2 )−I bond. A large variety of valuable o ‐iodobiaryls has been synthesized in satisfactory to good yields and their derivatization have been described too. Beyond the synthetic utility of this transformation, a DFT study provides insights on the mechanism of the key reductive elimination step, which is driven by an original transmetallation between palladium(II)‐halides complexes. Abstract : A new strategy based on the Catellani reactions has enabled the one‐pot synthesis of ortho ‐iodobiaryls starting from aryl iodides and bromides. Beyond the synthetic utility of this transformation (32 examples and 6 subsequent derivatizations), a DFT study provides insights on the mechanism of the reductive elimination step, which is driven by an original transmetallation between palladium(II)‐halide complexes.